Cell-in-cell phenomena of intracellular neutrophils in a recurrent pleomorphic xanthoastrocytoma - Fote, Gianna M.; Urgun, Kamran; Davies, Jordan; Himstead, Alexander S.; Gramajo-Aponte, Kevin; Lopez, Alexander; Hsu, Frank P.K.; Yong, William H. (Free Neuropathology, 2024)
We describe a case of a young patient with a recurrent pleomorphic xanthoastrocytoma (PXA) showing unusual cell-in-cell (CiC) phenomena. We observed mostly viable but also necrotic neutrophils engulfed within tumor cells. The recurrent tumor was immunopositive for BRAFV600E mutant protein and showed CDKN2 homozygous deletions typical of PXA. Both genetic alterations were also reported in the original primary tumor. Unlike the original tumor that was GFAP and Olig-2 immunopositive, the recurrent neoplasm was largely negative for GFAP and Olig-2 suggesting dedifferentiation. The large malignant cells that contained the neutrophils were negative for histiocytic and lymphohematopoietic markers. Whereas CDKN2 homozygous deletion is common in PXA, its presence is rare in histiocytic neoplasms. Both reactive astrocytes and glial neoplasms very rarely may engulf neutrophils in a process resembling emperipolesis or cellular cannibalism. Future work may clarify which type of CiC pathway is involved.